2021
DOI: 10.26803/ijlter.20.7.18
|View full text |Cite
|
Sign up to set email alerts
|

How Pre-service Teachers Learn Microbiology using Lecture, Animations, and Laboratory Activities at one Private University in Rwanda

Abstract: Observing classroom practices and checking the effect of instructional methods on academic achievement are crucial in the teaching and learning process. The present study was aimed at discovering the dominating pre-service biology teachers’ and instructors’ activities in microbiology classes and their respective effects when animations–based instructions and small-group laboratory activities are used. An equivalent time-series design was applied using a small group of participants in year two biology education… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The fact that female teachers performed more than their counterparts was a surprising authentic finding in this study since almost no available studies have investigated performance due to gender among teachers' classroom practices. In a similar study that investigated the performance among pre-service teachers, females showed a better performance than their male counterparts after having been taught with the lecture and lab methods; however, this was the opposite after having been taught utilizing the animation method (Mukagihana et al, 2021). A similar observation did not affect when secondary physics teachers did not visualize different teaching practices (Ndihokubwayo et al, 2020b).…”
Section: Discussionmentioning
confidence: 95%
“…The fact that female teachers performed more than their counterparts was a surprising authentic finding in this study since almost no available studies have investigated performance due to gender among teachers' classroom practices. In a similar study that investigated the performance among pre-service teachers, females showed a better performance than their male counterparts after having been taught with the lecture and lab methods; however, this was the opposite after having been taught utilizing the animation method (Mukagihana et al, 2021). A similar observation did not affect when secondary physics teachers did not visualize different teaching practices (Ndihokubwayo et al, 2020b).…”
Section: Discussionmentioning
confidence: 95%
“…These observations were not only found in physics instructions, but also in other STEM subjects. For instance, Mukagihana et al (2021) found that lectures and small-group laboratory-based activities dominated the main teaching of biology more than animations did. While using COPUS in chemistry instruction, Byusa et al (2020) argued that although teachers put students in groups, students were still learning passively since teachers simply moved around the groups without encouraging the students to complete the given activities.…”
Section: Instructors' and Students' Classroom Practices During The Ap...mentioning
confidence: 99%
“…Observing classroom practices to assess the effect of instructional methods on students' academic achievement is vital in teaching and learning (Mukagihana et al, 2021). The way sciences, in general, and physics, in particular, are taught do not motivate students to learn actively.…”
Section: Introduction 11 Background To the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Further, cooperative learning, student-centered method, and resource-based teaching methods were found to improve feelings toward biology subjects (Rabgay, 2018;Njoku & Nwagbo, 2020 ;Mukagihana et al, 2021b ). Therefore, factors such as gender would be of interest for researchers to well cater for both males and females inclusively.…”
Section: Introductionmentioning
confidence: 99%